Mathematics for Matriculation Semester 1 - Ong Beng Sim (Oxford Fajar Sdn., 2009)
Mathematics for Matriculation Semester 1 2nd Edition updated is a revised edition that offers a comprehensive and effective learning experience for students who are studying Mathematics at matriculation level. Written by experienced authors and based on the latest 2006 matriculation syllabus, the book has many features that will help students learn and understand important concepts in mathematics as well as prepare themselves for their examinations